Towards a self-powering greenhouse using semi-transparent PV: Utilizing hybrid BESS-hydrogen energy storage system - Gholami, Mohammadreza (2025)
Energy dependency and financial factors are crucial for the sustainability of greenhouse operations. This study presents two main contributions to the field: first, it investigates the integration of semi-transparent photovoltaic (STPV) technology with a hybrid battery energy storage system (BESS) and hydrogen (H2) storage in greenhouse applications. Second, by employing a comprehensive approach with the GBO algorithm, the research examines various scenarios as a multi-objective optimization problem, balancing economic considerations such as net present value (NPV) and energy dependency (ED). By leveraging the long-term storage capabilities of hydrogen—particularly during periods of surplus energy in summer—we aim to significantly reduce energy dependency in winter when STPV alone is insufficient. The findings reveal that the hybrid system significantly reduces ED, with reductions ranging from 61.82 % to as low as 1.56 % in winter. Financial analysis indicates that integrating STPV, BESS, and H2 can increase NPV up to $1,584,800 when focusing on maximizing profit. However, scenarios emphasizing minimal ED result in negative NPVs, underscoring the trade-offs between achieving energy independence and maintaining financial viability. This dual-focus optimization not only enhances the economic viability of greenhouse energy systems but also promotes sustainability and energy independence, providing valuable guidance for developing sustainable and financially viable greenhouse energy management strategies.